Disordered Eating: The Young Male Side. Issue 4 (2nd October 2018) - Ammann, Sabine; Berchtold, André; Barrense-Dias, Yara; Akre, Christina; Surís, Joan-Carles
ABSTRACT: Disordered eating (DE) is known to predominate among girls, and historically studies have focused primarily on them. This cross-sectional study aimed to investigate the characteristics of adolescent and young adult males at risk of DE. Participants (N = 2269; 15–24 years) in a study assessing their lifestyle were divided into two groups based on the SCOFF five-question screening tool: a SCOFF[+] group for participants at risk of disordered eating, and a SCOFF[-] group for everyone else. SCOFF[+] participants were more likely to be overweight and obese; have a lower socio-economic status and non-Swiss parents; experience weight issues; and report a chronic condition, poorer emotional well-being and a less positive attitude towards life. With 10% of males at risk of DE, clinicians should be aware of their specific characteristics, which should be considered red flags. DE is no longer a female-specific issue.